Ustekinumab – a new biological agent in the treatment of psoriasis - Salomon, Joanna; Szepietowski, Jacek (Dermatology Review/Przegląd Dermatologiczny, 2010)
Psoriasis is a chronic inflammatory disease, affecting about 2-3% of the general population. It is an important clinical problem due to high frequency and chronic course of the disease and the impossibility of complete recovery. Moreover, psoriatic arthritis may significantly influence the patients’ well-being. Recently, biological treatment has aroused great interest, being considered as opening a new era in psoriasis therapy. Ustekinumab is a human monoclonal antibody against the p40 unit of cytokines IL-12/IL-23. It prevents binding of these substances to IL-12Rb1 receptor and stops the inflammatory process. This paper presents the results of clinical trials on efficacy and safety of ustekinumab therapy. Ustekinumab, the newest biological agent, with a unique mechanism of action, seems to be very promising in the treatment of psoriasis and psoriatic arthritis. The results of studies performed so far indicate its high efficacy and excellent safety profile. Ustekinumab is administered subcutaneously in the dose of 45 mg/90 mg at week 0 and 4, then it is given every 12 weeks. The advantage of such therapy is its convenience, as it is administered only four times a year. This may be especially convenient for young people leading active social and professional lives. This therapy enables normal life without great involvement in a therapeutic process.